A Novel Preparation and Purification of Penta-Substituted 6-O-Propyl-b-cyclodextrin - Gan, Yongjiang (Asian Journal of Chemistry, 2014)
A synthetic process about propyl-b-cyclodextrins has been investigated through the reaction between b-cyclodextrin and dipropyl carbonate by anhydrous potassium carbonate as catalyst in DMF, penta-substituted 6-O-propyl-b-cyclodextrin was purified by silica gel chromatography. The structures of product were characterized by TLC, IR, MS, 1H NMR and 13C NMR. Mass spectra and 1H NMR proved the average degree of substitution of propyl-b-cyclodextrin is 5. 13C NMR proved the position of propyl at 6-position.